50 Years of integer programming 1958-2008 from the early years to the state-of-the-art - Jünger, Michael. (Springer Berlin Heidelberg, 2010)
I The Early Years -- Solution of a Large-Scale Traveling-Salesman Problem -- The Hungarian Method for the Assignment Problem -- Integral Boundary Points of Convex Polyhedra -- Outline of an Algorithm for Integer Solutions to Linear Programs An Algorithm for the Mixed Integer Problem -- An Automatic Method for Solving Discrete Programming Problems -- Integer Programming: Methods, Uses, Computation -- Matroid Partition -- Reducibility Among Combinatorial Problems -- Lagrangian Relaxation for Integer Programming -- Disjunctive Programming -- II From the Beginnings to the State-of-the-Art -- Polyhedral Approaches to Mixed Integer Linear Programming -- Fifty-Plus Years of Combinatorial Integer Programming -- Reformulation and Decomposition of Integer Programs -- III Current Topics -- Integer Programming and Algorithmic Geometry of Numbers -- Nonlinear Integer Programming -- Mixed Integer Programming Computation -- Symmetry in Integer Linear Programming -- Semidefinite Relaxations for Integer Programming -- The Group-Theoretic Approach in Mixed Integer Programming.